SELF-DEFENSE MECHANISM OF SUPPORTING CHARACTERS IN THE AFTER EVER HAPPY NOVEL - Nurahma Indah, Suhailah; Heriyati, Nungki (Proceedings of English Linguistics and Literature, 2020)
Literature entitled After Ever Happy written by Anna Todd is the last novel of After series. The novel mainly tells about the life of the main character Hardin who is known by the closest people around him as a troublemaker and rebellious. He cannot control his emotions whenever he faced problems. Damaging and rebelling can be categorized as defence mechanism as a way to protect himself. Hardin’s action give a substantial impact on his closest people such as Tessa, Vance, and Landon. The impact will be the main focus of this research. Employing defense mechanism theory by Freud the results of this study show that Hardin’s closest people are also used a defence mechanisms to respond to Hardin’s action. Thus to reduce the bigger problems that will arise, that can harm more people. the three supporting characters who felt the impact of Hardin's emotion use self-defense mechanism.